PENGARUH PENERIMAAN PAJAK DAERAH, RETRIBUSI DAERAH DAN SISA LEBIH PEMBIAYAAN ANGGARAN TERHADAP ALOKASI BELANJA MODAL PADA KABUPATEN DAN KOTA DI PROVINSI JAWA TIMUR - Penaten, Karolina Ina; Hariani, Lilik Sri; Wirshandono, Doni (Jurnal Riset Mahasiswa Akuntansi, 2017)
This study aims to determine the effect of local tax revenue, regional retribution and excess budget financing on the allocation of capital expenditure in districts and cities in the East Java province. The variables in this study are regional taxes, regional levies and excess budget financing as an independent variable and capital expenditure as the dependent variable. Analysis of the data in this study uses multiple regression statistical methods. Hypothesis test results show that local tax revenues and regional reductions do not have a significant effect on capital expenditure allocations while the remaining budget financing has a significant effect on capital expenditure allocations in the East Java province.